(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
With an ethnographic support a performative writing, this article argued about the fire juggling show Wiking: a sound battle. Was realize a descriptive analysis of the scene, complemented with Laban’s factors movement, articulated with a reflexive critical analysis based on Alessandro Fontana’s theories. The study highlighted that fire juggling has peculiarities called "limit variables", which influence the practice of the technique, and revealed that the junction between the circus disciplines used, the actions performed and the context of the presentation involves the e death, in both register: the imaginary and on the symbolic.